2020
DOI: 10.1371/journal.pgen.1008982
|View full text |Cite
|
Sign up to set email alerts
|

Gluconeogenesis and PEPCK are critical components of healthy aging and dietary restriction life extension

Abstract: High glucose diets are unhealthy, although the mechanisms by which elevated glucose is harmful to whole animal physiology are not well understood. In Caenorhabditis elegans, high glucose shortens lifespan, while chemically inflicted glucose restriction promotes longevity. We investigated the impact of glucose metabolism on aging quality (maintained locomotory capacity and median lifespan) and found that, in addition to shortening lifespan, excess glucose negatively impacts locomotory healthspan. Conversely, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Interestingly, high glucose (2% or 111 mM) treatment in young worms (1–3 days old) reduces lifespan, but beginning glucose treatment after worms are at a post-reproductive age (7 days old) extends lifespan ( Lei et al, 2018 preprint). A recent study found a direct effect of glucose metabolism on aging in worms, where glycolysis is detrimental to, and gluconeogenesis is beneficial to healthy aging, though not maximal longevity ( Onken et al, 2020 ). As glucose metabolism is evolutionarily conserved, it will be of interest to explore the role of glycolysis and gluconeogenesis in GSF-dependent lifespan extension in flies and vertebrate models.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, high glucose (2% or 111 mM) treatment in young worms (1–3 days old) reduces lifespan, but beginning glucose treatment after worms are at a post-reproductive age (7 days old) extends lifespan ( Lei et al, 2018 preprint). A recent study found a direct effect of glucose metabolism on aging in worms, where glycolysis is detrimental to, and gluconeogenesis is beneficial to healthy aging, though not maximal longevity ( Onken et al, 2020 ). As glucose metabolism is evolutionarily conserved, it will be of interest to explore the role of glycolysis and gluconeogenesis in GSF-dependent lifespan extension in flies and vertebrate models.…”
Section: Discussionmentioning
confidence: 99%
“…[46] In C. elegans, increased activity of PEPCK and another gluconeogenic enzyme, fructose-1,6-bisphosphatase, are each required for the longevity effects of CR. [47] This consumption of oxaloacetate to produce glucose should drive the AST reaction in the reverse direction, depleting aspartate (Reverse AST: AKG + Aspartate → Glutamate + Oxaloacetate).…”
Section: Aspartate Signaling and Caloric Restrictionmentioning
confidence: 99%
“…[ 46 ] In C. elegans , increased activity of PEPCK and another gluconeogenic enzyme, fructose‐1,6‐bisphosphatase, are each required for the longevity effects of CR. [ 47 ]…”
Section: Mechanisms Connecting the Tca Cycle To Aging And Longevitymentioning
confidence: 99%
“…To increase the knowledge about the cellular damage induced by these conditions, high-carbohydrate intake studies in C. elegans have been conducted in high-glucose diets that mimic the high-carbohydrate diets consumed by humans. One of the most intriguing results is the reduction of its lifespan and changes in several metabolic regulators that contribute to it exerting deleterious effects by which glucose decreases lifespan [ 21 ].…”
Section: Impacts Of Carbohydrate Metabolism On Lifespanmentioning
confidence: 99%
“…After glucose uptake, glycolysis is active in breaking down glucose and extracting energy or storing it in glycogen form. An analysis to determine whether glycolytic genes are associated with lifespan in C. elegans showed that of the three major irreversible regulatory enzymes of glycolysis, hexokinase (HXs), phosphofructokinase (PFK), and pyruvate kinase (PYK-1,2)-, both PFK and PYK knockdown extended the lifespan of C. elegans [ 21 , 30 , 31 ]; a similar effect was seen for glucose phosphate isomerase (GPI) and phosphoglycerate mutase (PGAM), which are also glycolytic enzymes ( Figure 2 ) [ 32 , 33 ]. This effect was probably due to the blockade of glucose metabolism, which likely altered the metabolic flux, reducing mitochondrial respiration or ATP synthesis, thereby increasing the lifespan, similarly to caloric restriction, although we cannot disregard that other pathways may be implicated in increasing lifespan.…”
Section: Impacts Of Carbohydrate Metabolism On Lifespanmentioning
confidence: 99%